An introduction to transnational criminal law - Boister, Neil, author (Oxford, U.K : Oxford University Press, 2012)
States criminalise many transnational offences, such as piracy, human trafficking, drug trafficking, terrorism, organised crime, and cybercrime. This book provides an introduction to this area of law, setting out what transnational crimes are, and how states can establish jurisdiction over them and enforce it.
What is transnational crime? -- What is transnational criminal law? -- Piracy and modern maritime safety offences -- Slave trading, human trafficking, and migrant smuggling -- Drug trafficking -- Terrorism -- Transnational organised crime -- Corruption -- Money laundering -- Emerging transnational crimes -- General principles of transnational crimes and punishments -- Jurisdication over transnational crime -- International law enforcement cooperation -- Law enforcement cooperation on the high seas -- Law enforcement cooperation through anti-money laundering and countering the financing of terrorism -- Legal assistance -- Extradition of transnational criminals -- Asset recovery -- Trends in transnational criminal procedure -- Institutions -- Implementation and compliance -- Transnational criminal law : some reflections
Includes bibliographical references and index
Keywords: International criminal law; Transnational crime; International criminal law